Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1530/erc-13-0054
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hormones for the treatment of cancer

Abstract: Four cardiac hormones, namely atrial natriuretic peptide, vessel dilator, kaliuretic peptide, and long-acting natriuretic peptide, reduce up to 97% of all cancer cells in vitro. These four cardiac hormones eliminate up to 86% of human small-cell lung carcinomas, two-thirds of human breast cancers, and up to 80% of human pancreatic adenocarcinomas growing in athymic mice. Their anticancer mechanisms of action, after binding to specific receptors on cancer cells, include targeting the rat sarcoma-bound GTP (RAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 131 publications
1
29
0
Order By: Relevance
“…This is supported by the co-localization of ANP and the Frizzled receptor observed on membrane of treated cells as well as by the evidences demonstrating the ability of ANP and Wnt1a in competing and displacing each other from the binding receptor [30]. Our results were sustained by data obtained by Vesely and collaborators, demonstrating that ANP and the other natriuretic hormones LANP, VSDL and KP are able to decrease the concentration of β-catenin up to 88% in human pancreatic cancer cells, up to 83% in human colorectal adenocarcinoma cells, and up to 73% in human renal adenocarcinoma cells [31]. The same Authors also reported that, in pancreatic, colorectal and renal cancer cells, all the four cardiac hormones reduce the concentration of the Wnt pathway activator WNT-3a [31] and decrease the levels of the Secreted Frizzled-related protein-3 (sFRP-3) [39], a secreted glycoprotein that affects Wnt signaling and that has been linked to tumor promotion in different types of cancers [40].…”
Section: Innovative Targets For Antitumor Activity Of Anpsupporting
confidence: 78%
See 1 more Smart Citation
“…This is supported by the co-localization of ANP and the Frizzled receptor observed on membrane of treated cells as well as by the evidences demonstrating the ability of ANP and Wnt1a in competing and displacing each other from the binding receptor [30]. Our results were sustained by data obtained by Vesely and collaborators, demonstrating that ANP and the other natriuretic hormones LANP, VSDL and KP are able to decrease the concentration of β-catenin up to 88% in human pancreatic cancer cells, up to 83% in human colorectal adenocarcinoma cells, and up to 73% in human renal adenocarcinoma cells [31]. The same Authors also reported that, in pancreatic, colorectal and renal cancer cells, all the four cardiac hormones reduce the concentration of the Wnt pathway activator WNT-3a [31] and decrease the levels of the Secreted Frizzled-related protein-3 (sFRP-3) [39], a secreted glycoprotein that affects Wnt signaling and that has been linked to tumor promotion in different types of cancers [40].…”
Section: Innovative Targets For Antitumor Activity Of Anpsupporting
confidence: 78%
“…This innovative aspect of ANP anticancer efficacy, is partially sustained by the results obtained by Vesely and collaborators, that demonstrated its effect on some components of the Wnt signaling [31]. …”
Section: Innovative Targets For Antitumor Activity Of Anpmentioning
confidence: 85%
“…Several in vitro studies have clearly indicated the cytotoxic effects of cardiac peptides against malignant cells. Based on studies performed by Vesely et al, four cardiac peptides including LANP, KP, VD and ANP demonstrate signi cant anti-proliferative effects against breast, prostate, lung, brain and renal carcinomas (Vesely, 2013). Reported by Sun et al, VD and KP demonstrate their anti-cancer activities in prostate cancer through inhibiting RAS activity (Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Vessel dilator blocks the cycle (Fig. ) by which these kinases and β ‐catenin stimulate each other to cause cancer cells to grow . The in vivo anticancer effects of vessel dilator described above were observed after s.c. infusion (ScI), but the pharmacokinetics of vessel dilator after ScI have not been determined.…”
Section: Introductionmentioning
confidence: 97%
“…Vessel dilator eliminates 33% of human pancreatic adenocarcinomas growing in mice when it is given s.c . The mechanism of action of vessel dilator within cancer cells involves multiple targets (Fig. ).…”
Section: Introductionmentioning
confidence: 99%